Proteome Changes Paralleling the Olfactory Conditioning in the Forager Honey Bee and Provision of a Brain Proteomics Dataset - Sialana, Fernando J.; Silva Menegasso, Anally Ribeiroda [UNESP]; Smidak, Roman; Hussein, Ahmed M.; Zavadil, Michael; Rattei, Thomas; Lubec, Gert; Palma, Mario Sergio [UNESP]; Lubec, Jana (Wiley-Blackwell, 2019)
The olfactory conditioning of the bee proboscis extension reflex (PER) is extensively used as a paradigm in associative learning of invertebrates but with limited molecular investigations. To investigate which protein changes are linked to olfactory conditioning, a non-sophisticated conditioning model is applied using the PER in the honeybee (Apis mellifera). Foraging honeybees are assigned into three groups based on the reflex behavior and training: conditioned using 2-octanone (PER-conditioned), and sucrose and water controls. Thereafter, the brain synaptosomal proteins are isolated and analyzed by quantitative proteomics using stable isotope labeling (TMT). Additionally, the complex proteome dataset of the bee brain is generated with a total number of 5411 protein groups, including key players in neurotransmitter signaling. The most significant categories affected during olfactory conditioning are associated with SNARE interactions in vesicular transport (BET1 and VAMP7), ABC transporters, and fatty acid degradation pathways.
Keywords: honeybee brain; olfactory conditioning; proboscis extension reflex; quantitative proteomics